LOGIKA EMPIRISME IBNU TAIMIYYAH DAN RELEVANSINYA TERHADAP STABILITAS EPISTEMOLOGI ISLAM - Muhammad Aviv Nafiudin (Living Islam: Journal of Islamic Discourses, 2024)
Islamic civilization in its golden age is a civilization built by the Islamic intellectual tradition with all its developments in intuitive, textual, rational, and empirical areas. However, while Islamic knowledge in the intuitive, textual, and rational areas can be witnessed today, it is not the case with knowledge concerning the empirical area which seems to sink from the paradigm of Islamic thought. Therefore, this research aims to explore the logical structure of Ibn Taymiyyah's empiricism and see its relevance to the stability of Islamic epistemology. To answer these questions, this study uses a qualitative method with the type of library research that refers to two works of Ibn Taymiyyah "Naqdh al-Manthiq" and "al-Radd 'ala al-Manthiqiyyin", while the theory used is the framework of empiricism epistemology. This study found that Ibn Taymiyyah's criticism of Aristotelian formal logic (deductive-syllogistic) which is deeply rooted in the Islamic intellectual tradition is the thing that led to the formulation of the empiricism logic. While Ibn Taymiyyah deconstructed the deductive style of thought, indeed at the same time he had formulated the logic of empiricism, that the essence of natural reality is everything as far as it is particular-concrete, which to capture it requires inductive reasoning in the form of sensory observation, particular syllogism, and analogical reasoning. Finally, this finding has its urgency and contribution to the stability and comprehensiveness of Islamic epistemology. Keyword: Epistemology; Naqdh al-Manthiq; al-Radd ‘ala al-Manthiqiyyin; Deductive; Inductive.   Peradaban Islam pada masa keemasannya adalah peradaban yang dibangun oleh tradisi intelektual Islam dengan segala perkembangannya baik dalam wilayah intuitif, tekstual, rasional, maupun empiris. Namun demikian, sementara ilmu pengetahuan Islam dalam wilayah intuitif, tekstual, dan rasional dapat disaksikan perkembangannya hingga dewasa ini, tidak halnya dengan pengetahuan yang menyangkut wilayah empiris yang seakan tenggelam dari paradigma pemikiran Islam. Oleh karenanya, penelitian ini bertujuan untuk menggali struktur logika empirisme Ibnu Taimiyyah dan melihat relevansinya terhadap stabilitas epistemologi Islam. Untuk menjawab persoalan tersebut, penelitian ini menggunakan metode kualitatif dengan model library research yang mengacu pada dua karya Ibnu Taimiyyah “Naqdh al-Manthiq” dan “al-Radd ‘ala al-Manthiqiyyin”, sementara teori yang digunakan adalah kerangka epsitemologi empirisme. Penelitian ini menemukan bahwa kritik Ibnu Taimiyyah terhadap logika formal Aristotelian (deduktif-silogistik) yang mengakar kuat dalam tradisi intelektual Islam adalah hal yang melatarbelakangi gagasan logika empirismenya. Sementara Ibnu Taimiyyah mendekonstruksi corak pemikiran deduktif tersebut, sungguh pada saat yang sama ia telah merumuskan logika empirismenya, bahwa hakikat dari realitas kealaman adalah segala sesuatu sejauh ia bersifat partikular-konkret, yang untuk menangkapnya diperlukan penalaran induktif yang berupa observasi indrawi, silogisme partikular dan penalaran analogis. Pada akhirnya, temuan ini memiliki urgensi dan kontribusinya tersendiri terhadap stabilitas dan komperhensifitas epistemologi Islam. Kata kunci: Epistemologi; Naqdh al-Manthiq; al-Radd ‘ala al-Manthiqiyyin; Deduktif; Induktif.